Prediction of mechanical stresses of single rotor blade of low pressure of Nasiriya power plant steam turbine (University of Thi-Qar Journal for Engineering Sciences, 2019)
In this paper, two types of stresses acting on the single rotor blade of low pressure steam turbine for Nasiriya power plant were studied. The first type of stresses was the stresses due to pressure force on the single rotor blade, while the second type of stresses are the centrifugal stresses. The stresses due the pressure force were studied in this paper at three loads (70, 140, 210 MW), while the pressures acting on the first rotor blade of steam turbine were 512, 3311.7, 6496.8 Pa respectively . In addition , the blade was fixed at the root and free at the end, while the rotational speed of blade was 341 rad/sec was applied as rotational load. The results showed that the rotational load has the greatest effect on the blade. Also the stresses due to rotational load are higher than stresses due to steam pressure at the three loads.